The Impact of Blended Learning on Students’ Performance and Satisfaction in South East European University (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Blended learning is a new way of teaching and learning. As the name implies it is a combination of classroom learning with the online learning platform. This way of learning enables students to partially control the process of learning. The study aims to find out the effect of blended learning on students’ performance and satisfaction. Students’ satisfaction with blended learning does not necessarily lead to students’ performance improvement. A structured questionnaire is used to gather data. Three hundred and nineteen (319) collected questionnaires were analysed using multivariate regression from structural equation modelling (SEM). Collected data were analysed using the SPSS statistical software and Smart PLS. The results of the analysis show that blended learning has an impact on both students’ performance and students’ satisfaction. The course management and interaction have a positive significant effect on students’ satisfaction and performance, with the latter having a stronger effect on both satisfaction and performance outcomes from blended learning.  Finally, the study shows that there is a correlation in on hand between blended learning and students’ improved performance, and on the other hand a positive correlation between satisfaction and performance.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.